2006
DOI: 10.1007/s11104-006-9085-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects, distribution and uptake of silicon in banana (Musa spp.) under controlled conditions

Abstract: Three contrasted genotypes of Musa spp. (M. acuminata cv Grande Naine, M. acuminata spp. Banksii and M. balbisiana spp. Tani) were grown for 6 weeks under optimal conditions in hydroponics and were submitted to a wide range of Si supply (0-1.66 mM Si) to quantify the Si uptake and distribution in banana, as well as the effect of Si on banana growth. The level of Si supply did not affect plant growth, nor the rate of water and nutrient uptake. The rate of Si uptake and the Si concentration in plant tissues incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
91
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 31 publications
17
91
3
2
Order By: Relevance
“…Our results are partly in agreement with previous studies: Henriet et al (2006) showed for banana plants, that plant growth was not influenced by the level of Si supply, similarly to the present study. The authors showed, however, that the rate of Si uptake by banana, as well as the Si content in plant biomass, were lowest (passive Si uptake) at high Si concentrations of the solution (1.7 mmol L -1 ) and higher than based on passive transport (active Si uptake) at lower Si concentrations (0.02-0.8 mmol L -1 ).…”
Section: Comparison Of Real and Theoretical Si-uptake Ratessupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are partly in agreement with previous studies: Henriet et al (2006) showed for banana plants, that plant growth was not influenced by the level of Si supply, similarly to the present study. The authors showed, however, that the rate of Si uptake by banana, as well as the Si content in plant biomass, were lowest (passive Si uptake) at high Si concentrations of the solution (1.7 mmol L -1 ) and higher than based on passive transport (active Si uptake) at lower Si concentrations (0.02-0.8 mmol L -1 ).…”
Section: Comparison Of Real and Theoretical Si-uptake Ratessupporting
confidence: 94%
“…The authors showed, however, that the rate of Si uptake by banana, as well as the Si content in plant biomass, were lowest (passive Si uptake) at high Si concentrations of the solution (1.7 mmol L -1 ) and higher than based on passive transport (active Si uptake) at lower Si concentrations (0.02-0.8 mmol L -1 ). This implies that plants in the study by Henriet et al (2006) had to "make efforts" for Si uptake only in case of low Si availability. This was not the case in the present study: Highest average Si concentrations in solutions occurred in the treatments with silica gel (Fig.…”
Section: Comparison Of Real and Theoretical Si-uptake Ratesmentioning
confidence: 99%
“…Silicon plays a very important role in the reduction of the plants vulnerability to biotic and abiotic environmental stress (Fauteux et al 2005, Mitani and Ma 2005, Ma and Yamaji 2006, Liang et al 2006, Gunes et al 2007, Sacała 2009). This component increases the plants' resistance to pathogens and pests (Samuels et al 1993, Fawe et al 1998, Raven 2003, Henriet et al 2006, Cai et al 2009). One of the most important beneficial effects of silicon on plant growth is related to increased resistance under water stress conditions (Ma et al 2004, Sacała 2009).…”
mentioning
confidence: 99%
“…Banana roots are able to induce silicate dissolution thereby increasing silicon availability in the rhizosphere (Hinsinger et al, 2001;Rufyikiri et al, 2004). In this respect, a study was conducted in hydroponic by Henriet et al (2006) (device 2) to investigate the effect of Si supply on banana growth, water uptake and nutrient uptake under optimal and sub-or non-optimal conditions (Fig. 6).…”
Section: Needlesmentioning
confidence: 99%
“…Quantitative model of water and silicon movement and distribution in the plant (from Henriet et al, 2006) of 0.0 (control), 0.08, 0.42, 0.83 and 1.66 mM, and to cover as much as possible the range of Si concentration that can be found in soil solutions (0.01-1.99mM). As described by Henriet et al (2006), Si was supplied as H 4 SiO 4 obtained by dissolving sodium metasilicate in demineralized water, followed by leaching on a protonated cation-exchange resin (Amberlite® IR-120). Neither Si precipitation nor H 4 SiO 4 deprotonation was expected because Si concentration was below the solubility limit (<1.79 mM Si) and pH ranged between 5 and 6.5 (Stumm & Morgan 1996).…”
Section: Needlesmentioning
confidence: 99%